The Identification of Eggs of Echinococcus by Immunofluorescence Using a Specific Anti-oncospheral Monoclonal antibody - Craig, P.S.; Macpherson, C.N.; Nelson, G.S . (The American journal of tropical medicine and hygiene)
A relatively simple and specific test has been developed to distinguish eggs of Echinococcus from those of other morphologically identical taeniid species. A specific anti-Echinococcus oncosphere monoclonal antibody was produced which binds in an indirect immunofluorescence test to egg-derived oncospheres of E. granulosus but not to those of other taeniid species, such as Taenia hydatigena, T. saginata, T. pisiformis, T. ovis, T. multiceps, or T. taeniaeformis. Specific fluorescence was obtained with oncospheres of E. granulosus derived from either hatch/activated viable eggs using artificial intestinal fluid or from hypochlorite/detergent treated eggs. The potential use of this test in the study of the transmission of Echinococcus in Turkana, Kenya, is discussed.
Keywords: Test; Eggs; Immunofluorescence test; Turkana; Kenya